PRAKTEK PEMBUATAN JEMBATAN KAYU BULAT SEDERHANA DI BEBERAPA KONSESI HUTAN DI KALIMANTAN - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1990)
An investigation on simple log bridge construction practices was carried out in five forest concession areas scattering in West, Central and South Kalimantan from 1987 to 1989. The purpose is to find current practices, the amount of log/ wood used and problems faced in constructing simple log bridges.It is obvious in the field that government guidance in planning, construction and maintenance of log bridges is still far from satisfaction. It is common to see that (I) the variation in bridge construction is large; (2) bridges are built to the strength far higher than required; (3) too many logs are used in bridge construction; (4) problems Of soil erosion around and under bridges are quite serious; (5) bridges are loaded with unnecessary heavy dirt and/ or gravel which may reduce the effective supporting capacity of stringers; and (6) quite often the bridge was washed out due to low construction.Effective guidance from the government in forest bridge planning, construction and maintenance is strongly needed in order to reduce excessive use of natural resources (logs), to maintain proper bridge function for longer period, and to minimize environmental disturbances. For this purpose, the invo!vement of civil engineers in handling various forest engineering problems and pacing of research activities are urgently needed.